2017
DOI: 10.7896/j.1709
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of long-term business relationships in the dairy value chain in transition countries: the case of Albania

Abstract: Building on transaction cost economics theoretical framework, we examined the determinants of long-term business relationships between farmers and buyers in the Albanian dairy chain in a context characterised by weak institutions and lack of formal contract. Logistic regression analysis was employed to test the model on primary data collected from a sample of 315 Albanian farmers engaged in the production of sheep and goat milk. The study results support our hypotheses that trust, uncertainty and levels are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The study relied on quantitative statistical analysis method by applying logistic regression model to identify the most important factors influencing the likelihood of domestic tourism in the Kingdom on foreign tourism. This model was selected since the dependent variable values are binary variables (preference for domestic tourism or foreign tourism) (Gerdoci, 2017). Logistic regression model was estimated by maximum likelihood method to overcome the problems that arise if the estimate using simple regression method of Ordinary Least Square (OLS).…”
Section: Methodsmentioning
confidence: 99%
“…The study relied on quantitative statistical analysis method by applying logistic regression model to identify the most important factors influencing the likelihood of domestic tourism in the Kingdom on foreign tourism. This model was selected since the dependent variable values are binary variables (preference for domestic tourism or foreign tourism) (Gerdoci, 2017). Logistic regression model was estimated by maximum likelihood method to overcome the problems that arise if the estimate using simple regression method of Ordinary Least Square (OLS).…”
Section: Methodsmentioning
confidence: 99%
“…The level of perception is also linked to uncertainty. Indeed, research shows that trust, uncertainty and investment in specific assets are key determinants of long-term relationships for Albanian farmers (Gërdoçi et al, 2017). The perceived level of uncertainty is influenced by the level of information that farmers have about challenges (e.g.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…The farmers' capacity and willingness to participate in F2S schemes is crucial not only for the F2S programmes but also in the framework of the consolidation of local markets. However, in transition economies, poor organisation of the value chain (weak vertical and horizontal cooperation) is a major challenge (Imami et al, 2013;Gërdoçi et al, 2017), making it more challenging to establish F2S. Despite the importance of local short food supply chains (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zeweld et al (2017) suggest that alternative information sources affect smallholder farmers’ behavioral intentions. Gerdoci et al (2017) used perceptual independent variables to predict long-term business relationships in the dairy value chain. Moreover, Tang et al (2015) studied market information to improve farmers’ production plans and found significant results.…”
Section: Theory and Framework Developmentmentioning
confidence: 99%